Air pollution in India: questions of advocacy and ethics. Issue 1 (1st January 2017) - Worthington, Roger P.; McLean, Michelle; Doshi, Neelam
Abstract: In large cities around the world, the effects of air pollution on human health present a growing problem. In this commentary, we assert that governments alone are not responsible for addressing such issues and health care professionals (HCPs) need to consider whether their duty of care should extend beyond normal clinical boundaries. When considering the ethics around the generation and effects of air pollution, especially in relation to justice and health care, actions taken by HCPs (e.g. in a country such as India) potentially extend beyond treating individual patients one-at-a-time for toxic effects of emissions and include advocating on behalf of others. While these problems are not unique to India, India is particularly badly affected by air pollution, and the situation there is made worse by large sectors of the population having limited access to health care, resulting in poor morbidity and mortality outcomes compared with other SE Asian countries. Using illustrative scenarios, we consider the effects of air pollution on present and future generations, recognising, however, that cause and effect are sometimes disconnected, with human behaviour in one place having far-reaching consequences in another place or at another time. Furthermore, the consequences of air pollution do not fall evenly across populations, and an injustice arises if economically challenged, vulnerable sectors of the population pay a price (in this case impaired health) for the actions of others. From a moral perspective, HCPs should be willing to look beyond their traditional role as 'healers' and advocate on behalf of others to help limit harms caused by this often invisible yet life-limiting and life-threatening form of pollution. This may require cultural change to existing models of health care, including the role of the HCP, to improve health security in India and elsewhere.